Education 3640. Problems and issues in special education. No. 25. Sexual abuse of children. - Nesbit, W. C. (Wayne C.), 1943- (Teacher); Karagianis, Leslie D. (Teacher); Memorial University of Newfoundland. Division of Educational Technology (Producer) (Memorial University of Newfoundland. Division of Educational Technology, 1987)
Dr. Karagianis discusses sexual abuse and interviews Cathy Knox, Assistant Crown Prosecutor in St. John's, about sexual abuse cases in Newfoundland. "Dr. L. Karagianis, Cathy Knox." Video ends abruptly